Cover Image. Issue 14 (1st September 2021) - Chandwani, Rahul; Kline, Julia E.; Harpster, Karen; Tkach, Jean; Parikh, Nehal A.; ,
Abstract : COVER ILLUSTRATION Corpus callosum fiber tractography in sagittal orientation derived using constrained spherical deconvolution (CSD) modelling. CSD is an advanced diffusion MRI technique that partially overcomes limitations of the diffusion tensor model and better represents white matter microstructure. CSD models the diffusion signal in each voxel as a function of the fiber orientation distribution, which can be used to perform more accurate tractography. We identified the corpus callosum as a key sensorimotor tract involved in the early development of cerebral palsy in infants born very preterm.